Digital Marketing-Based Tourism Planning Policy in Order to Realize Regional Tourism Competitiveness: (Study on Regional Tourism Development in East Java) - Kurniawan, Andy (Journal of Industrial Engineering & Management Research, 2022)
Planning products in the form of tourism are the main prerequisites for unifying the direction of tourism development in the regions. To further emphasize the direction and details of tourism development planning, regulations are needed that will cover the stages of activities contained in the plan product. One of the planning policies that can be done is the development of digital marketing-based tourism. In this study, problems were found in local government digital marketing activities, including processing customer data for retention and determining the KPIs needed as a reference for digital marketing strategies. The limitations of adequate tools or devices are also an obstacle in digital marketing. In addition, the lack of human resources. This study uses a descriptive qualitative approach, with data collection techniques using observation, interviews and documentation, as well as testing the validity of the data by triangulation of sources.